Gender equality results case study India enhancing energy based livelihoods for women micro entrepreneurs. (Gender equality results case studies., 2018)
Reliable supply of 24 hour electricity in the State of Madhya Pradesh since 2014 has transformed the lives of many, including women from low income households. An Asian Development Bank project Enhancing Energy Based Livelihoods for Women Micro-Entrepreneurs validates how women can be empowered through capacity development in efficient use of electricity and energy-based enterprises, and provision of business development services. The case study builds up on the project progress so far, showcasing women who, along with their sense of personal empowerment, have increased their incomes and savings through microenterprises. The case study reaffirms that a steady supply of electricity, coupled with capacity development, helps create an arena where men and women are accorded equal participation in business opportunities.